Analisis Dampak Faktor-Faktor yang Mempengaruhi Pengangguran Terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Dewi Ernita (Jurnal EMT KITA, 2023)
This study aims to determine and analyze whether there is an influence between Investment, Wages, Economic Growth and Inflation on the Open Unemployment Rate in Jambi Province in 2010-2021. This research is categorized as analytical research, which is a study that analyzes data that leads to a conclusion, a population, which is inferential. The data used in this study is secondary data obtained from government agencies, namely the Jambi Province BPS. The analytical tool used in this study is Multiple Linear Regression, with the results of the analysis as follows; There is significant effect between Investment on the Open Unemployment Rate in Jambi Province in 2003-2021, partial and the Wages, Economic Growth Rate and Inflation on the Open Unemployment Rate in Jambi Province in 2003- 2021 not significant partially there and not simultaneously. The magnitude of the influence of investment on the Open Unemployment Rate in Jambi Province in 2003-2021 is only partially 47,2%. The influence of wages on the level of open unemployment in Jambi Province in 2003-2021 is only partially -3,3%. The large influence of the Economic Growth Rate on the Open Unemployment Rate in Jambi Province in 2003-2021, partially only amounted to -0,22%. The big influence of Inflation on the Open Unemployment Rate in Jambi Province in 2003-2021 is only -0,92% partially. Simultaneously, the large influence of Investment, Wages, Economic Growth and Inflation on the Open Unemployment Rate in Jambi Province in 2003-2021 is 43,2%.